Enzymatic Degradation of Gracilariopsis lemaneiformis Polysaccharide and the Antioxidant Activity of Its Degradation Products - Fang, Tian (Mar Drugs, 2021)
Gracilariopsis lemaneiformis polysaccharides (GLP) were degraded using pectinase, glucoamylase, cellulase, xylanase, and β-dextranase into low-molecular-weight polysaccharides, namely, GPP, GGP, GCP, GXP, and GDP, respectively, and their antioxidant capacities were investigated. The degraded GLP showed higher antioxidant activities than natural GLP, and GDP exhibited the highest antioxidant activity. After the optimization of degradation conditions through single-factor and orthogonal optimization experiments, four polysaccharide fractions (GDP1, GDP2, GDP3, and GDP4) with high antioxidant abilities (hydroxyl radical scavenging activity, DPPH radical scavenging activity, reduction capacity, and total antioxidant capacity) were obtained. Their cytoprotective activities against H(2)O(2)-induced oxidative damage in human fetal lung fibroblast 1 (HFL1) cells were examined. Results suggested that GDP pretreatment can significantly improve cell viability, reduce reactive oxygen species and malonaldehyde levels, improve antioxidant enzyme activity and mitochondria membrane potential, and alleviate oxidative damage in HFL1 cells. Thus, the enzyme degradation of GLP with β-dextranase can significantly improve its antioxidant activity, and GDP might be a suitable source of natural antioxidants.